O efeito transformador das atividades lúdicas nas aulas de matemática - Bispo, Leandro Pinto (2014)
This work aims to analyze the results of the use of challenges and tricks based on mathematical principles as a motivational method in high school classroom. The activities contain elements that help to improving concentration, stimulate thinking ability, arouse interest in mathematics classes and thus increase participation of the students in the classroom. Each activity is described in detail, including a summary of its mathematical content, the average classroom time required, as well as a suggestion on how to perform it in class. Besides the direct assessment of the results by the teacher, a more objective evaluation of the e ects of these activities on the student's perception and attitude towards mathematics and its study was made by means of questionnaires answered by the students before and after the development of the project. Analysis of the data from the answers is also presented.